Donor Hemovigilance Programme in managing Blood Transfusion Needs: Complications of Whole Blood Donation (Journal of Pathology of Nepal, 2013)
Background: Hemovigilance like quality systems and audits have become an integral part of Blood Transfusion Services in the developed countries and has contributed greatly to its development. Hemovigilance begins with donors and must enable the collection of information on reactions occurring during the donation of blood, selections of donors and to prevent such incidents. The aim of study was to help identify the trends of adverse events , occurring in blood donors at a tertiary-care hospital, to recommend best practices to improve donor care and safety Materials and Methods: This record-based study was conducted on all adverse events related to allogenic whole blood donations performed over 24 months. All whole blood donations were analyzed. All adverse events occurring during or at the end of the donation were noted using a standardized format and analyzed determining significance at p